Fundamentals of database systems - Elmasri, Ramez (Addison-Wesley, 2011)
Bibliography: p.1099 - 1132; 11 parts (29 chapters): Databases and Database Users; Database System Concepts and Architecture; The Relational Data Model and Relational Database Constraints; Basic SQL; More SQL: Complex Queries, Triggers, Views, and Schema Modification;...